Implementasi Kebijakan Penerimaan Pajak Kendaraan Bermotor Dalam Meningkatkan Pendapatan Asli Daerah Provinsi Lampung - Siswanto, Hendra; Indriani, Indriani; Handayani, Agustuti; Irsandi, Irsandi; Rinova, Dora (e-JKPP, 2024)
This study examines the implementation of the motor vehicle tax revenue policy in enhancing Regional Original Income (Pendapatan Asli Daerah/PAD) in the Province of Lampung, with a focus on the role of the Provincial Revenue Agency (Badan Pendapatan Daerah/Bapenda). The research investigates how effectively the policy has been applied, identifies the challenges faced in its implementation, and evaluates its impact on PAD. The study reveals that while the policy is well-structured, its implementation is still not fully optimal. The target group, which consists of vehicle owners, has not yet fully complied with tax obligations, leading to a gap in revenue generation. Despite the relatively conducive environmental factors and collaboration among related institutions, bureaucratic procedures and unresponsive staff remain key barriers to achieving the policy's objectives. Furthermore, there is a lack of public awareness regarding the importance of timely tax payments. This study emphasizes the need for improvements in public service quality, staff responsiveness, and taxpayer compliance to meet the set targets and ultimately increase the effectiveness of the policy in contributing to PAD. The findings provide valuable insights for policymakers and local government agencies to refine the implementation strategy and optimize tax revenue collection in the region.